(SELF)FORMATION OF LITHUANIAN NATIONAL IDENTITY IN IRELAND: A DISCOURSE OF EDUCATIONAL POLITICIANS, EDUCATIONAL PRACTITIONERS, AND PUPILS - Strolytė, Agnė (Acta Paedagogica Vilnensia, 2013)
This article covers the (self)formation of Lithuanian pupils’ national identity in Ireland and reveals their attitude towards their national identity. A review of the Irish education policy documents has shown the prevailing intercultural education model in Ireland, which should guarantee equal rights of national identity and development for all pupils. However, analysis of interviews with politicians-experts and practicians has shown that in practice some difficulties occur when implementing the objectives declared by the Irish education documents. The implementation of educational policy objectives mainly depends on the attitude and effort of a school or teachers. This is why the implementation of intercultural education has been different in the Irish secondary schools studied. The analysis of experts-practicians’ interviews has revealed assimilative objectives of educational policy towards the immigrants. The education of immigrants in Irish secondary schools is more oriented to their successful integration but not to the nurturance of national identity. Nevertheless, there are some possibilities and conditions for the (self)formation of national identity in Irish secondary schools. However, the preservation and nurturance of national identity does not depend on the support of education institutions but on the attitude of the family and pupils’ motivation.Pupils’ questionnaires have benefited to reveal that Lithuanians’ national identity is strong, and no features of national identity hybridisation or fragmentation have been found. The data of the research have shown the ability of Lithuanian pupils to sustain several layers of cultural dependence: they successfully integrate into the new society, simultaneously retaining their national identity.
Keywords: national identity; emigration; Irish education policy; intercultural education